Incidence, complications and management of Meckel’s diverticulum - Pattanaik, S. K.; Dandpat, B. P.; Mishra, J. M. (International Surgery Journal, 2017)
Background: The incidence of complications of Meckel’s diverticulum is decreasing over years. Whether symptomatic or asymptomatic, it is often diagnosed intraoperatively. Controversy exists as regards the method of its operative removal and more so the safety and efficacy of its removal if found incidentally. Methods: A three years prospective and three years retrospective study was undertaken in 125 diverticula found by 3726 laparotomies. Intraoperative findings, type of operation, postoperative management, histopathology and complications in both complicated and asymptomatic diverticula were analyzed. Results: Male to female ratio was 3:2. Found in 3.4% of surgical population, 23 (18.4%) were defined to have complications and 102 were incidental. Complications decreased as the age advanced falling to zero after age 60. Meckel’s diverticulitis, peptic ulcer and umbilical sinus were common in childhood and intestinal obstruction was common in adults. Patients with ectopic mucosa mostly gastric had more complications. 42.2% of incidental cases underwent surgery due to early age, narrow and long diverticula. In both the groups, segmental resection was preferred to simple diverticulectomy. Ectopic tissue could not be substantiated by feeling the induration or thickening of wall. Mortality and morbidity in symptomatic group was 8.7% each and in incidental group 0% and 4.6% respectively. Conclusions: Intestinal obstruction and inflammatory pathology are common complications, gastric mucosa being common association. Narrow and long diverticula in young should be excised prophylactically with zero mortality and acceptable morbidity to prevent further complications.